Botulinum toxin A versus microwave thermolysis for primary axillary hyperhidrosis: A randomized controlled trialCapsule Summary - Gabriela Lladó Grove, MD; Katrine Togsverd-Bo, MD, PhD, DMSc; Claus Zachariae, MD, PhD, DMSc; Merete Haedersdal, MD, PhD, DMSc (Elsevier, 2024)
Background: Botulinum toxin A (BTX) and microwave thermolysis (MWT) represent 2 treatment modalities for axillary hyperhidrosis with different procedural and efficacy profiles. Objective: To compare long-term outcomes following BTX vs MWT treatment of axillary hyperhidrosis. Methods: A prospective, randomized, within-patient, controlled trial, treating axillary hyperhidrosis with contralateral BTX and MWT. Objective sweat measurement and patient-reported outcome measures for sweat and odor were collected at baseline, 6-month and 1-year follow-up (6M/1YFU). Hair reduction and patient treatment preference was also assessed. Results: Sweat reduction was significant (all P <.01) for both interventions throughout the study. Objectively, sweat reduction was equal at 1-year FU (ΔP =.4282), but greater for BTX than MWT at 6-month FU (ΔP =.0053). Subjective sweat assessment presented comparable efficacy (6MFU: ΔP =.4142, 1YFU: ΔP =.1025). Odor reduction was significant (all P <.01) following both interventions, whereas only sustaining for MWT (6MFU: ΔP =.6826, 1YFU: ΔP =.0098). Long-term, hair reduction was visible after MWT, but not BTX (ΔP ≤.0001), and MWT was preferred by the majority of patients (76%). Limitations: The intrinsic challenges in efficacy assessment. Conclusion: This study exhibited BTX and MWT with similar sweat reduction, but distinguishable odor and hair reduction at 1-year FU. These findings support individualized treatment approaches for axillary hyperhidrosis based on patient-specific symptoms and preferences.